Gypenosides Prevent and Dissolve Cholesterol Gallstones by Modulating the Homeostasis of Cholesterol and Bile Acids - Zhuang, Qian; Cheng, Jinnian; Xia, Jie; Ning, Min; Wu, Shan; Shen, Shuang; Shi, Yan; Huang, Dan; Dong, Zhixia; Wan, Xinjian (Frontiers in Medicine, 2022)
Gypenosides (GPs), obtained from Gynostemma pentaphyllum (Thunb.) Makino, have been traditionally prescribed to treat metabolic disorders in Asians. This study assessed whether GPs could prevent lithogenic diet (LD)-induced cholesterol gallstone (CG) formation and enhance CG dissolution in mice. Gallstone-susceptible C57BL/6J mice were fed an LD or normal chow, with or without GPs. Bile acids (BAs) in gallbladder bile were analyzed by liquid chromatography-tandem mass spectrometry. Differentially expressed hepatic genes were identified by RNA sequencing, followed by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses. GPs were found to prevent LD-induced CG formation and to dissolve pre-existing LD-induced CGs. GPs reduced total cholesterol levels and increased BA levels in bile, as well as reducing the BA Hydrophobicity Index, ratio of 12α-hydroxylated (12α-OH) to non-12α-OH BAs, and Cholesterol Saturation Index in gallbladder bile. GO and KEGG pathway enrichment analyses indicated that GPs-induced genes were involved in BA biosynthesis and cholesterol metabolism. GPs increased the hepatic expression of genes encoding the cytochrome P450 (Cyp) enzymes Cyp7a1, Cyp7b1 and Cyp8b1, while decreasing the hepatic expression of genes encoding the adenosine triphosphate-binding cassette (Abc) transporters Abcg5 and Abcg8. GPs may be a promising strategy for preventing and dissolving CGs.